Competence and Authorization of the Security Service Of Ukraine as a Subject to Anti-Corruption and Organized Crime - O. O. Voronyi (Bulletin of Kharkiv National University of Internal Affairs)
The author of the article summarizes theoretical approaches to defining the concepts of authority and competence.